Factors Influencing Motivation in Online Arabic Learning of Indonesian Older Man - Mahfuz Rizqi Mubarak; Noor Amalina Audina; Nurul Wahdah; Hamidah Hamidah; Aulia Mustika Ilmiani (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2021)
Changes in the offline learning system to online learning have an effect on the demotivation of students to learn. However, this fact does not affect an elderly Indonesian male. This study aims to explore motivational factors for these elderly men in participating in an online Arabic learning program organized by an informal institution in Indonesia. A narrative research design was used in this study. The data was extracted through in-depth interviews. The results showed that there were several factors that influenced the motivation to learn Arabic online from elderly men, namely: Motivation to understand Al-Qur'an, motivation from friends, and presentation of interesting Arabic material. These findings suggest further research on the motivation to learn Arabic online by involving elderly participants of various genders.